IDENTIFIKASI FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI DAN PARTISIPASI MASYARAKAT KABUPATEN BANTUL DALAM KEPESERTAAN PROGRAM JKN-KIS - Nur Fitri Mutmainah, Ferri Wicaksono (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2018)
The aim of this paper is to identification factors that can influence perception and participation of Bantul's citizen to be participant of JKN-KIS. The highest participant of JKN-KIS in Bantul becomes background of this paper. Descriptive qualitative approach is used to explain objective, detail, comprehensive and deeply about the observation and the deept interview activities. Observation, documentation, and in deepth interview technique are used by author to collect sources of data that are needed in this research. The conclution of the research shows that 4 factors effect perception and participation of Bantul's citizen become JKN-KIS member, such as first sosial environment, second government persuasion, third institusional of health public services and the fourth personal experience.